(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
The intensive use of the Internet platforms establishes new perspectives on the social and political function of the media. This article focuses on the possibilities of alternative mobilizing actions, involving the participation of citizens around issues related to the conflicts of society and nature. We use the concept of net-activism (DI FELICE, 2012), with its features online network action. The objective is to highlight the role of the online platforms for forwarding public petitions of Avaaz.org and Change.org, the two most accessed platforms in Brazil, around social and environmental claims. After submitting the theoretical frameworks, we described the platforms, and selected 22 campaigns to perform an interpretative analysis, based on the arguments they use for demands and struggles, followed by a typology proposed by Castells (2018). In the end, it is possible to understand, even partially, the role of this social-environmental activism around online petitions.